A comparative study of morbidity pattern in elderly of rural and urban areas of Allahabad district, Uttar Pradesh, India - Verma, Vandana; Prakash, Shiv; Parveen, Khurshid; Shaikh, Shama; Mishra, Neha (International Journal Of Community Medicine And Public Health, 2017)
Background: The ageing process is a biological reality which has its own dynamics, largely beyond human control. The aged population has specific health problem that basically differs from those of an adult or young men. The aim was to study the socio demographic profile and pattern of morbidity in the elderly people of Allahabad district in Uttar Pradesh, India. Methods: A cross sectional study was carried out on elderly aged 60 years and above; selected from urban and rural areas of Allahabad district by multistage random sampling and were interviewed using pre tested schedule. Data analysis was done on SPSS 16 version. Results: A total of 400 elderly were surveyed (Male=215 and Female=185). Majority were Hindus (95.7%),) lived in joint families (59%), illiterate (43.75%), were either retired or not working (53%), and belonged to lower class (34.75%). The most common morbidities reported among them were ocular problems (68.5%), followed by musculoskeletal (59.7%), and psychological problems (29.75%). The urban elderly had significantly higher proportion of psychological problems (35%), diabetes (23.5%), hypertension (39%) and obesity (35%) whereas prevalence of anemia (43%) and malnutrition (38.5%) and respiratory problems (16%) were more common in rural area. Conclusions: Over all the study showed that prevalence of certain diseases such as diabetes, hypertension, obesity, and psychological problems was more in urban elderly whereas the prevalence of anemia, under-nutrition, respiratory and skin problems were more in rural elderly.